Perancangan Mesin Pencacah Biji Jagung Dengan Mata Pisau Sebagai Pemecah - Nasirwan, Nasirwan; Fadhlurrahman, Zaki; Wahyu Widodo, Tri; Rosa, Yazmendra; Yuli Y (Manutech : Jurnal Teknologi Manufaktur, 2024)
The corn grain chopping machine has been designed with a knife blade as a breaker. This designed machine will be used to process agricultural products. The machine design process begins with stages, namely data processing, drawing sketches, calculations, and drawing with solidwork. It is planned that the driving force for the corn seed chopper machine will be to use an electric motor with 4 HP power and 2800 Rpm rotation with specifications for length 890 mm, width 420 mm, height 757 mm. The capacity of the corn grain chopper machine is 213 kg/hour using a shaft made of ST-37 steel and a direct transmission system and the bearings used are 1 inch in size. The way this chopping machine works is by utilizing the rotation of the electric motor to rotate the blade as a breaker and relying on the machine's cutting speed of 2800 rpm which makes the work process fast. The resulting corn fragments come out of the output hole provided and then enter the container provided. The specifications of the design results are obtained in accordance with the original plan